The Effectiveness of Empiric Transarterial Glue Embolization (TAGE) of Gastroduodenal Artery (GDA) for Bleeding Duodenal Ulcer: A Retrospective Study - Lee, Wil Sern; Ong, Hui Jun; Chua, Zi Wei; Loh, Kok Beng (The Interventionalist Journal, 2024)
ABSTRACT: Purpose To conduct a clinical audit on clinical outcome of empiric transarterial glue embolization (TAGE) of gastroduodenal artery (GDA) for bleeding duodenal ulcers to evaluate treatment efficacy. Materials and Methods All patients treated for bleeding duodenal ulcers between June 2019 and June 2023, in a single tertiary center (Penang General Hospital) were identified based on intervention radiological reports. Patients with bleeding duodenal ulcers underwent empiric transarterial glue embolization (TAGE) of gastroduodenal artery (GDA) following endoscopic hemostasis were included. Information was extracted from patients’ medical records, endoscopic and radiological reports. Data was computed and analyzed using Statistical Package for Social Sciences (SPSS). Results During the study period, a total of 26 patients were planned for empiric transarterial glue embolisation (TAGE) of gastroduodenal artery (GDA) for bleeding duodenal ulcer. The median age was 68 with 68% male (n=18) and 32% female (n=8). A total of 25 patients with duodenal ulcers of Forrest 1a (n=5), 1b (n=12), 2a (n=4), 2b (n=3) and 2c (n=1) who successfully underwent prophylactic TAGE of GDA were included in this study. It has a high technical success rate of 96.2% (n=25) with only one case of failure in cannulation due to tortuous arterial anatomy. Clinical success rate amongst the 25 patients who successfully underwent empiric TAGE of GDA was 84% (n=21) with only four patients developed rebleeding and required repeated endoscopic clipping. One of the four patients succumbed secondary to refractory bleeding. Conclusion Empiric transarterial glue embolisation (TAGE) of gastroduodenal artery (GDA) can be a useful adjunct treatment option in high risk bleeding duodenal ulcer with high technical and clinical success.